Disclosure of Sustainability Report on Financial Performance - Derry Ridwan Fauzi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
The increasing number of companies that publish sustainability reports in Indonesia has led to an increasing trend of research on the relationship between sustainability reports and financial performance. However, the results of these studies are still inconsistent. Re-examining the relationship between the sustainability report disclosure and financial performance is the aim of this study. Two things that make this study different from the previous one, the first study uses companies that consistently report sustainability reports, and the second, use financial performance measures, profitability. The sample used was 33 observations from companies that consistently reported sustainability reports during the 2017-2019 period. The test results show that the social dimension (SO) of the sustainability report has no effect on financial performance, while the other two dimensions, namely the environment (EN) and the Economy (EC), have a positive effect on financial performance.